Chlamydiosis in animals - Caspe, Sergio Gaston (2024)
The Chlamydiaceae family consists of Gram-negative, obligate intracellular bacteria that replicate within the cells of a diverse range of hosts. These hosts include domesticated animals such as cats, dogs, and livestock, as well as wildlife like koalas and birds, exotic species such as reptiles and amphibians, and humans. Chlamydial infection can result in various clinical signs, including respiratory diseases, reproductive failures, ocular pathologies, and enteritis, though the infected organism may remain asymptomatic. In recent years, chlamydial nomenclature has undergone several revisions due to the wide range of hosts, the frequent discovery of novel strains, and the reclassification of existing ones. Given this and the clinical significance of these infections, ranging from asymptomatic to fatal, an updated review is essential. This article outlines key characteristics of Chlamydia species and provides an updated overview of their nomenclature, offering a concise reference for future research on chlamydial diseases.